Conversion of Carbohydrate Biomass to γ‐Valerolactone by using Water‐Soluble and Reusable Iridium Complexes in Acidic Aqueous Media. Issue 7 (11th June 2013) - Deng, Jin; Wang, Yan; Pan, Tao; Xu, Qing; Guo, Qing‐Xiang; Fu, Yao
<x xml:space="preserve">Abstract</x> Mild‐mannered manipulation: A catalytic method for the conversion of carbohydrate biomass to γ‐valerolactone in acidic aqueous media has been developed. The water‐soluble iridium complexes were observed to be extremely catalytically active for providing γ‐valerolactone in high yields with high TONs. The homogeneous catalysts can also be recycled and reused by applying a simple phase separation process.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>